Mengupas Sebuah Pendekatan Normatif dalam Mengembangkan Studi Islam - Aliyah, Nur Fatin; Mawardi, Kholid (TSAQOFAH, 2025)
Basically, Islam is not merely a religion but also encompasses other components such as culture and knowledge that underlie it. As a religion, Islam has many dimensions that include faith, logic, economics, science and technology, environmental issues, history, and household life. Its broad scope allows Islam to embrace all differences that have become a reality of social and societal dynamics. It is not appropriate to interpret Islam using only one approach; instead, multiple approaches are necessary to allow Islam to permeate deeply and serve as a solution to every problem that arises in the realm of human life. Interpreting Islam normatively follows a deductive way of thinking, which starts from a belief that is considered true and certain, as all teachings originating from God are inherently true. Thus, they are not questioned but begin with belief, which is then reinforced by evidence and arguments.